2005
DOI: 10.1016/j.jretconser.2005.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Interaction effects of mood induction and nominal representation of price on consumer choice

Abstract: Gamble, A. (2005). Perception of Value of Money in Unfamiliar Currencies Department of Psychology, Göteborg University, Sweden.The real value of money as well as the perceived value of money is subject to changes. Inflation and deflation are examples of changes in real value. It has been shown that these changes do not always correspond to changes in subjective value. The money illusion implies that the subjective value of money is biased by the nominal representation in times of inflation or deflation. This t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 56 publications
0
11
1
Order By: Relevance
“…For instance, in an experiment where participants were confronted with hypothetical choices of consumer products, with prices in fictitious currencies with different nominal values Gamble et al (2005; for similar findings, see Soman et al 2002) demonstrated that more expensive products equipped with additional attractive features were chosen more often in a low nominal value currency than in a high nominal value currency. Soman et al (2002) tested the possibility of a reversal of the effect of the nominal value, arguing that not only prices but also salaries are considered in making economic decisions.…”
Section: Empirical Findingsmentioning
confidence: 86%
See 2 more Smart Citations
“…For instance, in an experiment where participants were confronted with hypothetical choices of consumer products, with prices in fictitious currencies with different nominal values Gamble et al (2005; for similar findings, see Soman et al 2002) demonstrated that more expensive products equipped with additional attractive features were chosen more often in a low nominal value currency than in a high nominal value currency. Soman et al (2002) tested the possibility of a reversal of the effect of the nominal value, arguing that not only prices but also salaries are considered in making economic decisions.…”
Section: Empirical Findingsmentioning
confidence: 86%
“…In a similar vein, Gamble et al (2005) showed that mood has a moderating influence on the effect of the nominal value. These authors demonstrated a stronger influence of the nominal value on choices of currency for paying for a product or receiving a salary when participants were in a positive mood than when they were in a negative mood.…”
Section: Accuracy-effort Tradeoffmentioning
confidence: 88%
See 1 more Smart Citation
“…This umbrella term refers to a series of transient asymmetries that can be observed when different groups of participants are asked to perform the same judgment or choice task in a different currency (Aalto-Setälä and Raijas 2003;Gamble et al 2002Gamble et al , 2005Jonas et al 2002;Raghubir and Srivastava 2002;Soman et al 2002;Tyszka and Przybyszewski 2006). The mere difference between the nominal values of two different currencies in which the same price-related task is performed (for instance, the euro and the Italian lira) produces asymmetries in consumers' intuitive judgments or choices, despite the fact that the real value of money is the same.…”
Section: The Euro Illusionmentioning
confidence: 99%
“…Furthermore, with the aim of examining effects of the nominal representation, the price increases were expressed in the same currency, either actual currencies (Swedish Crowns or Euros) or fictitious currencies with different units. As in several previous experiments (Gamble, 2006;Gamble et al, 2002Gamble et al, , 2005, the fictitious currencies were used to prevent confounding the effect of the nominal representation with effects of expectations or other effects of familiarity with the currency. The participants were presented the current prices and the prices a year ago, a time span which has been found not to impair memory substantially (Kemp, 1991).…”
Section: Introductionmentioning
confidence: 99%